Islamic Inheritance Law and Its Implications on the Rights of Adopted Children in IndonesiaPerspective on Adopted Children Enforcement in The Law of Inheritance - Megawati Atiyatunnajah; Sidik Setyawan (LEGAL BRIEF, 2023)
Adoption has developed into a widespread phenomenon in the context of Indonesian society. Due to the fact that adoption affects the interests of individuals within a family, adoption has been integrated into the legal framework that regulates family relationships As a result of the way it influences individual interests within the family, it has been incorporated into the legal framework governing family relationships. Article 39 of the Child Protection Law, adoptive parents must pay attention to the best interests of the child during the process, which must also be carried out in accordance with community habits, applicable laws and regulations. There are two categories of adoption in Indonesia: domestic adoption, which occurs between Indonesian citizens, and international adoption, which involves children of Indonesian citizens who are adopted by people who are not residents of Indonesia. The research method used is known as normative juridical research. This research method is used to understand and evaluate whether a legal regulation has complied with the applicable legal principles and formal requirements set by the law. The author chooses this method because it is relevant to various fields of law and generates new ideas. According to research, the inheritance rights of indigenous Indonesians are carried out based on Islamic law in situations involving Indonesian inheritance law. Adopted children are still considered biological parents and are not entitled to inherit from their adoptive parents. The local customary law system will determine how many adopted children are entitled to inheritance. Adopted children still receive inheritance from their biological parents, not from their adoptive parents because adopted children do not inherit from their adoptive parents. Increased public awareness and stricter regulations in Indonesia regarding adoption practices can help protect the rights and interests of children and promote safer and more secure adoption practices.